2017
DOI: 10.1590/2177-6709.22.2.095-105.oar
|View full text |Cite
|
Sign up to set email alerts
|

Do different vertical positions of maxillary central incisors influence smile esthetics perception?

Abstract: INTRODUCTION: The purpose of this study was to determine the perception of smile esthetics among orthodontists and layperson, with respect to different maxillary central incisors vertical positions in full-face and close-up smile analyses. METHODS: Frontal photographs of the smiles of two adult women were used. Images were altered to create a symmetrical image with the gingival margin levels of the maxillary canines matching the central incisors and a 1.0-mm central-to-lateral incisal step. Later, the images w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 26 publications
1
35
2
6
Order By: Relevance
“…As an example Kokich et al evaluated the perceptions of the dental professionals and the laypersons to bilateral crown length alterations; they reported that the threshold for unattractiveness was 1.0 mm for orthodontists, 1.5 mm for general dentists, and 2.0 mm for laypeople. This variation extends to the perception of asymmetric gingival margin between orthodontists and laypersons by 0.5 mm and 1 mm, respectively . Frontal occlusal canting perception was difficult for both preclinical and clinical students; both groups had high perception threshold.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…As an example Kokich et al evaluated the perceptions of the dental professionals and the laypersons to bilateral crown length alterations; they reported that the threshold for unattractiveness was 1.0 mm for orthodontists, 1.5 mm for general dentists, and 2.0 mm for laypeople. This variation extends to the perception of asymmetric gingival margin between orthodontists and laypersons by 0.5 mm and 1 mm, respectively . Frontal occlusal canting perception was difficult for both preclinical and clinical students; both groups had high perception threshold.…”
Section: Discussionmentioning
confidence: 75%
“…This variation extends to the perception of asymmetric gingival margin between orthodontists and laypersons by 0.5 mm and 1 mm, respectively. 30 Frontal occlusal canting perception was difficult for both preclinical and clinical students; both groups had high perception threshold.…”
Section: Discussionmentioning
confidence: 97%
“…The concepts of smile attractiveness and smile design have become popular in dentistry. Smile attractiveness is strongly affected by several factors, such as the shape, size, and color of the teeth, teeth arrangement, the space between the teeth, and the surrounding structures (lips and gums) [1,2]. Occlusal cant and gingival display have also been proved to have a strong impact on smile aesthetics [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Hier wird ein "möwenartiger" Schneidekantenverlauf [9] als harmonisch empfunden, was bedeutet, dass die seitlichen Schneidezähne inzisal 1-1,5 mm kürzer sein sollten als die mittleren (▶abb. 9) und sich damit eine flügelschlagartige Silhouette wie die einer Möwe ergibt [18]. In Ergänzung dazu neigen sich die Zahnachsen der Frontzähne tendenziell nach distal im Vergleich zur Senkrechten auf die Kauebene (▶abb.…”
Section: Dentale Analyseunclassified